9x+26+7x-17=2x+9(-3x)+5x

Simple and best practice solution for 9x+26+7x-17=2x+9(-3x)+5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x+26+7x-17=2x+9(-3x)+5x equation:


Simplifying
9x + 26 + 7x + -17 = 2x + 9(-3x) + 5x

Reorder the terms:
26 + -17 + 9x + 7x = 2x + 9(-3x) + 5x

Combine like terms: 26 + -17 = 9
9 + 9x + 7x = 2x + 9(-3x) + 5x

Combine like terms: 9x + 7x = 16x
9 + 16x = 2x + 9(-3x) + 5x

Remove parenthesis around (-3x)
9 + 16x = 2x + 9 * -3x + 5x

Multiply 9 * -3
9 + 16x = 2x + -27x + 5x

Combine like terms: 2x + -27x = -25x
9 + 16x = -25x + 5x

Combine like terms: -25x + 5x = -20x
9 + 16x = -20x

Solving
9 + 16x = -20x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '20x' to each side of the equation.
9 + 16x + 20x = -20x + 20x

Combine like terms: 16x + 20x = 36x
9 + 36x = -20x + 20x

Combine like terms: -20x + 20x = 0
9 + 36x = 0

Add '-9' to each side of the equation.
9 + -9 + 36x = 0 + -9

Combine like terms: 9 + -9 = 0
0 + 36x = 0 + -9
36x = 0 + -9

Combine like terms: 0 + -9 = -9
36x = -9

Divide each side by '36'.
x = -0.25

Simplifying
x = -0.25

See similar equations:

| 2a-4+5a-6= | | (15+n)-4=28 | | 8.58=(8p)/2 | | 0.2x-0.5x=0.1x+8 | | x*x+7x+10= | | (7.4X)+(1/5X)-(3/2)=(4/5X) | | 2xsquared+3x-15=0 | | 4.5(x-8)=13.5 | | 20=4xw | | (7/4)+(1/5)x-(3/2)=(4/5)x | | 2/5y+3=-3/5y | | 0=w^2+5w-456 | | r+3t=s | | 11+I=14 | | 2x^2+16-18=54 | | 2/5b=-4 | | 3t+r=s | | Y=9-5(2) | | 2x^2+16-18=0 | | X/10=-8/5 | | 4-p-p-p-p+2p= | | (-6/7)(6m+4)=(5/28)m-17 | | y^3-3y^2-10y+30= | | 5/4+a=7/9 | | 7x+32+2x+4=180 | | -5x+3=26+4 | | (32+x)-10=3x | | 50=5000/12*r | | 2=14-2h | | (-2+3a)/(9a^2-4) | | 4x-x+5=3x-9 | | 10x+90=100 |

Equations solver categories